Drawing with Art‐Well‐Being: Intergenerational Co‐Creation with Seniors, Children and the Living Museum. (25th August 2021) - Burke, Geraldine; Alfrey, Laura; Hall, Clare; O'Connor, Justen
Abstract: This article explores how the Museum, Art and Wellbeing project brought primary school children and seniors from the same local community together to engage in explorative activities designed to reveal individual and mutual assets for wellbeing. The Museum, Art and Wellbeing project undertook a participatory arts‐based approach to investigate how the assets of a large public institution such as Museums Victoria, Australia could reach out and engage different community groups. The seniors came from a local University of the Third Age (U3A) which offers a wide range of classes but does not usually engage with primary schools. Children at the primary school engage in art learning and separate wellbeing learning but these age‐stage sessions, as designated to incremental year levels, had not previously included direct involvement of seniors in learning activities. For both groups, the connection to Victoria's state museums is marked by previous occasional one‐off visits. Museum resources have not been considered as ongoing assets for wellbeing that link to the local community in the way that this project does. The university's role in brokering such connections by deploying often ignored human/institutional assets to support health and strengthen community has been explored in papers by fellow researchers, Justen O'Connor and Laura Alfrey. Our enquiry is extended in this article by focusing on how art education, specifically art‐making, and intergenerational learning can strengthen community and enhance wellbeing across school and community‐based educational contexts and museums.